Towards Sustainable Agricultural Stewardship: Evolution and Future Directions of the Permaculture Concept. (1st February 2014) - Suh, Jungho
Abstract : This paper traces the origins of the concept of permaculture and discusses the sustainability of permaculture itself as a form of alternative agriculture. The principles of permaculture are shown to have many views and perspectives in common with Taoism and with Buddhist ecology and economics. The amalgamation of these Oriental traditions can be translated into the Kaya equation and beyond. It is argued that future permaculture movements should focus on revitalising the communitarian spirit of traditional farming villages instead of building intentional communal communities. The paper also calls for more aggressive environmental-policy measures that support permaculture and internalise the non-market value of reduced fossil-fuel energy consumption and waste recycling.